EFEKTIVITAS ETIKA BISNIS ISLAM DALAM MEMBANGUN KEPERCAYAAN DI ERA EKONOMI DIGITAL DALAM PERSPEKTIF SEJARAH ISLAM - Arum, Hafidza Sanshia; Azzaki, Adnan (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2024)
The phenomenon crisis of trust in today's digital economy is increasingly surfacing due to lack of transparency, data manipulation, and unethical business practices, especially in the e-commerce and fintech sectors. This research aims to explore the relevance and applicability of the principles of Islamic business ethics-honesty, fairness, justice, and equity. principles-honesty, fairness, social responsibility, and the prohibition of usury-as a solution to build trust in global digital business. solution to building trust in global digital business. The method used is a descriptive qualitative approach through literature review and content analysis to identify how Islamic ethical values content analysis to identify how Islamic ethical values can be implemented in the digital business environment. The research results show that the principles of honesty and transparency are very important to increase consumer consumer trust, especially in the delivery of product information and protection of personal data. Corporate social responsibility implementation has proven to be able to strengthen reputation and provide tangible benefits to society. society. In addition, the prohibition of usury is an important foundation in creating economic justice in Islamic fintech business models. creating economic justice in the sharia fintech business model that prioritizes profit-sharing schemes. business model that prioritizes profit-sharing schemes. This research recommends the principles of principles of Islamic business ethics as a strong foundation to face the ethical challenges and trust crisis in the digital era. ethical challenges and crisis of trust in the digital era.